Readiness of Health Workers to Provide Pregnancy Planning Program for Women Infected with Human Immunodeficiency Virus: A Case Study in Surabaya, East Java, Indonesia - Made Chindy Dwiyanti Marheni Putri; Pudji Lestari; Muhammad Ilham Aldika Akbar (Althea Medical Journal, 2021)
Background: The prevalence of human immunodeficiency virus (HIV) mother-to-child infection, or vertical transmission of HIV, in Indonesia is about 90%. Ministry of Health of the Republic of Indonesia Regulation No. 21 of 2013 stated that HIV infection in sexual productive age needs integrative professional help to lower the transmissions, including voluntary counseling and testing for pregnant women as well as all people at risk. This study aimed to determine the readiness of health workers to provide pregnancy planning program service for women with HIV.Methods: This study was a descriptive study involving 30 obstetricians and 30 residents of Obstetrics and Gynecology specialist education in Surabaya, Indonesia. The respondents’ knowledge on pregnancy planning for HIV-infected women based on based on guidance released by the Ministry of Health of Indonesia in 2017 and Regulation of Ministry of Health no. 52 the year 2017, as well as their attitude and readiness to provide pregnancy planning services, was explored. Questionnaires were distributed from August to December 2019 and the data collected were analyzed using Statistical Package for the Social Science (SPSS) version 17.0 and results were described in percentage.Results: Most health workers (80%) had good knowledge on providing pregnancy planning program for HIV positive women; however, only 63.3% had good attitude towards it. The majority of respondents (90%) were ready to help HIV patients in planning their pregnancy. Conclusion: Health workers in Surabaya are ready to provide services related to pregnancy planning for women infected with HIV.